Improved Management Effectiveness of a Marine Protected Area through Prioritizing Performance Indicators. Issue 2 (3rd March 2016) - Pendred, Sarah; Fischer, Andrew; Fischer, Sarah
ABSTRACT: The management success of a marine protected area (MPA) is essentially a social construct because people have differing views on what defines success. Conflicting opinions between stakeholders need to be identified and resolved to ensure these factors do not interfere with successful functioning of MPAs. This study looked at developing and prioritizing performance indicators for Maria Island Marine Nature Reserve (MIMNR), Australia. Performance indicators were developed for MIMNR based on an expert-led, structured framework and then prioritized using the Analytic Hierarchy Process (AHP), with respect to input from key informants of stakeholder groups. Results showed that all stakeholder groups agreed that management of MIMNR should first focus on "abundance and size of native species, " and that managers, fishers, and environmental nongovernmental organizations place a significantly higher priority on ecological over socioeconomic and governance performance indicators. Researchers placed even emphasis across all priorities. Results suggest that MIMNR should first focus on monitoring "abundance and size of native species" and demonstrates the capacity of the AHP to increase management effectiveness and improve the decision-making process. Furthermore, by identifying where discrepancies in preferences exist, the outcomes of this research can be used to enhance collaboration among stakeholders.